Equitable Digital Taxation for Inclusive Revenue Mobilization (Open Society Conference, 2025)
The rapid expansion of the digital economy had outpaced the capacity of traditional tax systems, particularly in developing countries. Although digital platforms generated substantial income, their contributions to public finance remained limited due to jurisdictional and structural gaps in existing tax regimes. This study aimed to explore digital taxation not solely as a fiscal mechanism, but as a strategic policy tool to enhance social inclusion. A qualitative doctrinal and comparative legal method was employed to analyze global digital taxation trends and compare them with national practices in selected developing countries, with a focus on Indonesia. The study proposed a framework that integrated digital tax policy with inclusive development goals, grounded in the theories of fiscal justice and inclusive governance. The findings revealed that aligning tax policy with the digitalization of the economy could enhance equity and state capacity in delivering public services. The research concluded with a normative-analytical model that could assist policymakers in designing fair, socially responsive, and development-oriented digital tax systems in an increasingly digital global landscape.